2003
DOI: 10.1128/jvi.77.11.6546-6550.2003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Epstein-Barr Virus Infections in Healthy Individuals

Abstract: We employed a newly developed genotyping technique with direct representational detection of LMP-1 gene sequences to study the molecular epidemiology of Epstein-Barr virus (EBV) infection in healthy individuals. Infections with up to five different EBV genotypes were found in two of nine individuals studied. These results support the hypothesis that multiple EBV infections of healthy individuals are common. The implications for the development of an EBV vaccine are discussed.Multiple Epstein-Barr virus (EBV) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
95
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 48 publications
(58 reference statements)
6
95
1
1
Order By: Relevance
“…(45). The oral cavity is also a reservoir for EpsteinBarr virus infection in healthy individuals (40,43). Other herpesviruses, such as HHV-6 and HHV-7, are also present in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…(45). The oral cavity is also a reservoir for EpsteinBarr virus infection in healthy individuals (40,43). Other herpesviruses, such as HHV-6 and HHV-7, are also present in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 It seems unlikely that sterilizing immunity against EBV can be achieved via vaccination because 1 to 10 virus particles are enough for the establishment of lifelong ␥-herpesvirus infections, 51,52 and reinfection of healthy EBV carriers with new EBV strains has been documented. 53,54 Thus, more recent immunotherapeutic approaches against primary EBV infection have concentrated on inducing T-cell responses to aid in asymptomatic seroconversion, rather than preventing infection, and to target EBVassociated malignancies. Along these lines, a single CD8 ϩ T-cell peptide epitope-based vaccine for IM has been tested in a phase 1 clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some studies examined the EBV termini and reported monoclonal expansion of EBV in several kinds of lymphoma (14,29). However, in contrast to the pattern in tumor cells, multiple EBV strains were observed in peripheral blood from patients with NPC and from asymptomatic EBV carriers (11,19,39,42), as determined based on variations in LMP1 genes. These findings suggest that EBV might infect the progenitor cell before cell proliferation and then undergo monoclonal expansion in tumor cells, thereby contributing to pathogenesis.…”
mentioning
confidence: 90%